Indications and findings of upper gut endoscopy in pediatric patients - Hasanah, Annisa'; Mandiricha, Tara (Intelektual Pustaka Media Utama, 2024)
Children undergoing more gastrointestinal endoscopies without the necessary indications risk serious adverse effects. Therefore, upper GI (UGI) endoscopy examination requires selective indications to minimize the risk of unnecessary use of UGI endoscopy. This study aimed to analyze the indications for endoscopy based on the main UGI complaints in pediatric patients at Dr. Saiful Anwar General Hospital Malang. A retrospective analysis of the first diagnostic endoscopy in children was conducted between July 2022 to July 2023 at Dr. Saiful Anwar General Hospital Malang. Among 60 patients were included with an age of 0-15 years old; 51.7% were boys and 48.3% were girls. The results showed recurrent abdominal pain (RAP) as the primary cause of UGI endoscopic indications (38.3%), followed by blood vomiting (33.3%), acute abdominal pain (21.6%), and prolonged vomiting (6.66%). In conclusion, recurrent abdominal pain in children is the most typical reason for upper gastrointestinal endoscopy, and persistent gastritis is the most typical underlying condition.